If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -4(m + -2) = 21 Reorder the terms: 15 + -4(-2 + m) = 21 15 + (-2 * -4 + m * -4) = 21 15 + (8 + -4m) = 21 Combine like terms: 15 + 8 = 23 23 + -4m = 21 Solving 23 + -4m = 21 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + -4m = 21 + -23 Combine like terms: 23 + -23 = 0 0 + -4m = 21 + -23 -4m = 21 + -23 Combine like terms: 21 + -23 = -2 -4m = -2 Divide each side by '-4'. m = 0.5 Simplifying m = 0.5
| 18y=15y^2 | | 6+2p-2=9p+5-6p | | 12x+36-8(x+12)=-24 | | 5x^2+7x-7=11-2x | | x^2+21x+90= | | -5n-6(-4n-1)=-103 | | g-3=2-5g | | 10c-(c-18)=-9 | | 0.04x-0.44=0.02x | | 9-16X=5X+3 | | 7x^2+13x-4=20-9x | | 16X-9=5X+3 | | 2x^2-28x=-6x^2-5x-14 | | x^2-20x-96=0 | | r^2+4=-4r | | 2p+3y+4y=27 | | x-1/5=x+5/15 | | 2b+b-3=1.5 | | m^2+18=9m | | -78=-6(-2+3a) | | N^2-3n=10 | | 5X+3=16X-9 | | x^2-18+45=0 | | 25=-4x | | 4x-8*2=36 | | (7x+4)(3x^2-20x-7)=0 | | 70=5(5x+1) | | (10x+3)(3x^2-20x-7)=0 | | 10+3x=22 | | 6a^2-11a=-4 | | x+x+2x=17-2x+1 | | 21=2t+9 |